SIRT5 deficiency enhances the proliferative and therapeutic capacities of adipose‐derived mesenchymal stem cells via metabolic switching. Issue 5 (23rd September 2020) - Ou, Tiantong; Yang, Wenlong; Li, Wenjia; Lu, Yijing; Dong, Zheng; Zhu, Hongming; Sun, Xiaolei; Dong, Zhen; Weng, Xinyu; Chang, Suchi; Li, Hua; Li, Yufan; et al.
Abstract: Background: Mesenchymal stem cells (MSCs) have therapeutic potential for multiple ischemic diseases. However, in vitro expansion of MSCs before clinical application leads to metabolic reprogramming from glycolysis to oxidative phosphorylation, drastically impairing their proliferative and therapeutic capacities. This study aimed to define the regulatory effects of Sirtuin 5 (SIRT5) on the proliferative and therapeutic functions of adipose‐derived MSCs (ADMSCs) during in vitro expansion. Methods: ADMSCs were isolated from wild‐type (WT) and Sirt5‐knockout (Sirt5 −/− ) mice. Cell counting assay was used to investigate the proliferative capacities of the ADMSCs. Dihydroethidium and senescence‐associated β‐galactosidase stainings were used to measure intracellular ROS and senescence levels. Mass spectrometry was used to analyze protein succinylation. Oxygen consumption rates and extra cellular acidification rates were measured as indicators of mitochondrial respiration and glycolysis. Metabolic‐related genes expression were verified by quantitative PCR and western blot. Hind limb ischemia mouse model was used to evaluate the therapeutic potentials of WT and Sirt5 −/− ADSMCs. Results: SIRT5 protein levels were upregulated in ADMCs during in vitro expansion. Sirt5 −/− ADMSCs exhibited a higher proliferation rate, delayed senescence, and reduced ROS accumulation. Furthermore, elevated protein succinylation levels were observed in Sirt5 −/− ADMSCs, leading to the reduced activity of tricarboxylic acid cycle‐related enzymes and attenuated mitochondrial respiration. Glucose uptake, glycolysis, and pentose phosphate pathway were elevated in Sirt5 −/− ADMSCs. Inhibition of succinylation by glycine or re‐expression of Sirt5 reversed the metabolic alterations in Sirt5 −/‐ ADMSCs, thus abolishing their enhanced proliferative capacities. In the hind limb ischemia mouse model, SIRT5 −/− ADMSCs transplantation enhanced blood flow recovery and angiogenesis compared with WT ADMSCs. Conclusions: Our results indicate that SIRT5 deficiency during ADMSC culture expansion leads to reversed metabolic pattern, enhanced proliferative capacities, and improved therapeutic outcomes. These data suggest SIRT5 as a potential target to enhance the functional properties of MSCs for clinical application. Abstract :